An Alternative to the Human Hemoglobin Test in the Investigation of Bloodstains Treated with Active Oxygen: The Human Glycophorin A Test - Ana Castelló; Francesc Francés; Fernando Verdú (The Scientific World Journal)
In criminal investigations, there are three stages involved when studying bloodstains: search and orientation, confirmation, and individualization. Confirmatory tests have two aims: to show that the stain contains a human biological fluid and to confirm the type of biological fluid. The need to determine the nature of the evidence is reflected in the latest bibliography, where the possibility of employing mRNA and miRNA markers for this purpose is proposed. While these new proposals are being investigated, the kits for determining human hemoglobin currently provide a simple solution for resolving this issue. With these kits, the possibility of obtaining false positives and false negatives is well known. However, recently, a new problem has been detected. This involves the interference caused by new cleaning products that contain sodium percarbonate (or active oxygen) when determining human hemoglobin. With the aim to resolve this problem, this work studied the ability of the human glycophorin A test to determine human blood in samples that have been treated with active oxygen. Our results show that the human glycophorin A test has a greater resistance to the destructive effect of the new detergents containing active oxygen; consequently, it provides an alternative to be taken into consideration in the confirmatory diagnoses of bloodstains.